Forming national identity in Iran the idea of homeland derived from ancient Persian and Islamic imaginations of place - Mozaffari, Ali (I.B. Tauris, 2014)
Ali Mozaffari explores the complex processes involved in the formation of Iranian national identity, laying particular stress upon the importance of place to ideas of homeland and the creation of a collective national identity. An important work that offers powerful insights into the forces shaping national identity in Iran.